2004
DOI: 10.1152/ajpcell.00099.2004
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine-induced calcium signaling and expression of adrenoceptors in avian tendon cells

Abstract: Sympathetic efferent nerves are present in tendons, but their function within tendon is unknown. alpha(1)-Adrenoceptors are expressed by a variety of cell types. In the presence of norepinephrine (NE), adrenoceptors activate G(q/11) signaling pathways that subsequently increase intracellular Ca(2+) concentration ([Ca(2+)](ic)). It was hypothesized that avian tendon cells express functional adrenoceptors that respond to NE by increasing [Ca(2+)](ic). Avian tendon cells were analyzed for mRNA expression of alpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 50 publications
3
7
0
1
Order By: Relevance
“…Additionally, these same tenocytes demonstrate immunoreactions for alpha-adrenergic receptors (11). Similar findings have been reported for avian flexor tenocytes, which demonstrated mRNA expression of alpha-adrenergic receptors (47). Stimulation of avian tenocyte cultures with noradrenaline resulted in a wave of calcium signaling within tenocytes (47).…”
Section: Production and Response Of Neurotransmitters In Tendonsupporting
confidence: 82%
See 1 more Smart Citation
“…Additionally, these same tenocytes demonstrate immunoreactions for alpha-adrenergic receptors (11). Similar findings have been reported for avian flexor tenocytes, which demonstrated mRNA expression of alpha-adrenergic receptors (47). Stimulation of avian tenocyte cultures with noradrenaline resulted in a wave of calcium signaling within tenocytes (47).…”
Section: Production and Response Of Neurotransmitters In Tendonsupporting
confidence: 82%
“…Similar findings have been reported for avian flexor tenocytes, which demonstrated mRNA expression of alpha-adrenergic receptors (47). Stimulation of avian tenocyte cultures with noradrenaline resulted in a wave of calcium signaling within tenocytes (47). It is therefore possible that noradrenaline may lead to downstream responses such as tenocyte proliferation and/or modulation of extracellular matrix production.…”
Section: Production and Response Of Neurotransmitters In Tendonsupporting
confidence: 77%
“…The activation of these channels permit calcium (Ca 2+ ) and other ions (e.g., sodium and potassium) to influx followed by membrane depolarization (Sackin, 1995). Norepinephrine treatment of avian tendon cells increased the expression of functional adrenoceptors by increasing intracellular Ca 2+ concentration (Wall et al, 2004). Cyclic stretching stimulated Ca 2+ influx into osteoblastic cells (Vadiakas and Banes, 1992), and laminar fluid flow increased intracellular Ca 2+ in human disc cells (Elfervig et al, 2001).…”
Section: Article In Pressmentioning
confidence: 99%
“…However, a recent study showed the expression of a functional α 1A -AR in primary tendon fibroblasts [11]. In rat-1 cells, a transformed cell line from embryonic fibroblast, expressing different subtypes of α 1 -AR, phenylephrine (PE), an α 1 -AR agonist, activates phospholipase D and releases arachidonic acid [12].…”
Section: Introductionmentioning
confidence: 99%